Ответы и объяснения

2014-03-12T14:01:51+04:00
1) y`= u`v+uv`
 y`=((6x+1)^4)` * (x+3) + ((6x+1)^4) * (x+3)`  = 4*(6)^3*(x+3)+((6x+1)^4) * 1=
=864x+2592 + ((6x+1)^4) - не уверена. не думаю, что такой ответ получится
2) y`= 5(9x^2-1)^4
3)y`=(3x-1)` * (x^3+2)  + (3x-1) * (x^3+2)`=3 * (X^3+2) +(3x-1)*(3x^2) =3x^2+6+9x^3-3x^2=
=6+9x^3

5) y`=3(5x^4)^2
6) y` = Cos3
4) y`=u`v-uv`/v^2 y`= ((3x^4-2)`(x^3+1) - (3x^4-2)(x^3+1)`) / (X^3+1)^2
я могла решить неверно. сравни с одноклассниками.
спасибо огромное)